2004
DOI: 10.1177/135945750401800203
|View full text |Cite
|
Sign up to set email alerts
|

Turn-Taking in Music Therapy with Children with Communication Disorders

Abstract: In a well-functioning dialogue, the nonverbal and often implicit visual and auditory cues ensure good continuation without interruptions or overlapping speak. In mutual interplay, both partners participate in turn-organisation, and therefore an analysis of cues indicating turn-taking and turn-yielding can provide information about the participants' social skills, whether or not the dialogue is verbal. This article presents relevant concepts from conversation analysis literature in order to analyse music therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 17 publications
2
37
0
2
Order By: Relevance
“…Therefore, the result provided some evidence that the therapists were able to follow the direction of treatment protocol. Holck (2004b) pointed out that musical turn-taking often consisted of imitation and variation. In this study, initially it was the therapist who imitated what the participant did in order to build empathic mutuality of interaction with the participant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the result provided some evidence that the therapists were able to follow the direction of treatment protocol. Holck (2004b) pointed out that musical turn-taking often consisted of imitation and variation. In this study, initially it was the therapist who imitated what the participant did in order to build empathic mutuality of interaction with the participant.…”
Section: Discussionmentioning
confidence: 99%
“…Holck (2002) suggested that music therapists use 'response evoking techniques' that involve creating mutually meaningful and enjoyable musical interaction themes in relation to the child's expression and focus of attention. These offer the potential for drawing the child's attention towards joint musical engagement.…”
mentioning
confidence: 99%
“…Music therapy has a long history of use as an intervention for children with ASD, particularly with those who have severe difficulties with social engagement (Reschke‐Hernandez ). Music therapy with children with ASD has been influenced by diverse learning theories from discrete trial training (Lim & Draper ) to relationship‐based approaches (Holck ). Music therapists adopting a relationship‐based approach typically use flexible improvisation methods to create opportunities for reciprocal interactions, affect sharing, turn taking and joint attention within live music making (Geretsegger et al .…”
mentioning
confidence: 99%
“…Music therapists can use "response evoking techniques" that create mutually meaningful and enjoy- 168 health psychology report able musical interaction themes in relation to the child's expression and focus of attention (Holck, 2002). By involving the child without requesting an immediate specific response, the therapist creates the opportunity to accept the rhythmic and melodic meanings tuned to his behavior.…”
Section: Discussionmentioning
confidence: 99%
“…It is a child-centered approach that utilizes mainly non-verbal musical interaction and thus is comparable with early reciprocal interaction between mother and infant (Hughes, 1995;Holck, 2004aHolck, , 2004bPavlicevic, 1997;Robarts, 1996;Trolldalen, 2005). As an intervention procedure, IMT makes use of the potential for social engagement and expression of emotions occurring through improvisational music making (Geretsegger, Holck, & Gold, 2012;Geretsegger, Elefant, Mòssler, & Gold, 2014).…”
Section: Introductionmentioning
confidence: 99%